Origin of mass and strong coupling gauge theories (SCGT15) proceedings of the Sakata Memorial KMI Workshop (World Scientific Publishing Co. Pte Ltd., 2018)
"This volume contains contributions to the workshop, which was largely focused on the strong coupling gauge theories in search for theories beyond the standard model, particularly, the LHC experiments and lattice studies of conformal fixed point. The main topics include walking technicolor and the role of conformality in view of the 125 GeV Higgs as a light composite Higgs (technidilaton, and other composite Higgs, etc.). Nonperturbative studies like lattice simulations and stringy/holographic approaches are extensively discussed in close relation to the phenomenological studies. After the discovery of 125 GeV Higgs at LHC, the central issue of particle physics is now to reveal the dynamical origin of the Higgs itself. One of the possibilities would be the composite Higgs based on the strong coupling gauge theory in the TeV region, such as the technidilaton predicted in walking technicolor with infrared conformality. The volume contains, among others, many of the latest important reports on walking technicolor and related subjects in the general context of conformality, in a way of direct relevance to the LHC phenomenology as well as the lattice studies. It is very timely to study full theoretical implications in the exciting era when the LHC is vigorously working. This volume is of great importance for that purpose. Speakers of 40 talks (plus posters) include K-I Aoki, Y Aoki, K Bamba, E Bennett, R S Chivukula, H Georgi, A Hasenfratz, D-K Hong, K Itoh, D Elander, G Fleming, H Fukano, Y Iwasaki, M Jarvinen, D Kadoh, S Kim, R Kitano, K-I Kondo, J Kuti, D Lin, N Maru, H Matsufuru, S Matsuzaki, K-I Nagai, C Nonaka, H Ohki, E Pallante, M Rho, E Rinaldi, F Sannino, D Schaich, A Shibata, R E Shrock, E H Simmons, K Tuominen, C H Wong, N Yamada, M J S Yang, and K Yamawaki."--
Description based on online resource; title from PDF title page (viewed December 6, 2017)
Keywords: Gauge fields (Physics) / Congresses; Higgs bosons / Congresses; Particles (Nuclear physics) / Congresses; Electronic books